Grannoye Ukho Settlement in the Ulyanovsk Volga Region - Gismatulin Marat R. (Археология евразийских степей, 2023)
The article presents the results of studies of the Grannoye Ukho settlement, located on the territory of the Sengileevskie Mountains National Park. This site was discovered in 2015, its study was continued in 2017. Archaeological materials received as a result of reconnaissance allow author to refer the Grannoye Ukho settlement to the Post-Maklasheevka culture of the Ananyino cultural and historical area. Ceramic complex of the settlement is closer to the materials from the sites of the Post-Maklasheevka culture, located in the southern part of the Republic of Tatarstan and the north of the Ulyanovsk region. The site is probably dated to the second half of the 6th–5th centuries BC. Grannoye Ukho settlement is the only known settlement of the Post-Maklasheevka culture in the Ulyanovsk Volga region, it is explained, first of all, by the poor study of the region.